Factors Related to Nurses’ Work Stress in the Toto Kabila Hospital - Suwarly Mobiliu1, Ratnawati2, Lisdiyanti Usman2, Lusiane Adam2, Fatmawati Mohamad2, Fifi Ishak3, Dew (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stress at work can not be avoided, nurses are at risk of experiencing work stress. The purpose of this study is to find factors related to the nurse’s work stress. This type of research was observational analytic using a cross-sectional study design. The sample was 96 nurses working in the Toto Kabila hospital. Data were analyzed using chi-square tests. The marital status (p-value=0.001), length of work (p-value=0.001), working conditions (p-value=0.004), social support (p-value=0.010) had significant relationship with work stress. The results of this study are expected to be used as input and consideration for nurses at Toto Kabila Hospital to maximize how to deal with stress.